Srategi Membangun Kemandirian Guru Madrasah Berbasis Pesantren Dalam Desain Pembelajaran - Mardia, Mardia; Toha, Rahmawati (Universitas Negeri Makassar, 2025)
The aim of this research-based service is to improve the pedagogical competence of teachers in designing learning in Islamic boarding schools based madrasah in Pinrang. The dedication method used is a Workshop and mentoring based on Participatory Action Research. In implementing the service action plan, the researcher becomes a facilitator in terms of: 1) Providing workshops or training in learning design and preparation of learning tools to teachers in Islamic boarding schools based madrasah in Pinrang Regency. 2) Provide assistance for Islamic boarding school-based Madrasah throughout Pinrang Regency to develop learning tools. The results of community service show that teachers' pedagogical competencies need to be trained so that their skills increase, so that teachers are able to create active, innovative, creative, effective and fun learning for students. In addition, teachers have the ability to independently explore their own potential in empowering and managing education in a competitive and comparative way.